A novel multidisciplinary bio- and geo-chronological approach for age determination of Palaeolithic bone artifacts in volcanic settings: An example from eastern Sabatini, Latium, Italy. (18th May 2017) - Petronio, Carmelo; Ceruleo, Piero; Marra, Fabrizio; Pandolfi, Luca; Rolfo, Mario F.; Salari, Leonardo; Sottili, Gianluca
Abstract: In this study, we provide combined biochronologic and chronostratigraphic constraints to the fluvial-lacustrine succession cropping out near the village of Rignano Flaminio, 35 km north of Rome, where two bone instruments have been recovered along with several vertebrate fossil remains. The presence of bone tools is characteristic of the Latium region, whereas it is rare in the rest of Italy, but very few sites in which such artifacts occur have precise geochronological constraints. In the investigated site, the presence of Cervus elaphus eostephanoceros, among other taxa, indicates a time interval limited to Marine Isotopic Stage (MIS) 13 and MIS 11. The occurrence of the Tufo Rosso a Scorie Nere pyroclastic-flow deposit, dated 449 ± 2 ka, at the base of the sedimentary deposits hosting the faunal assemblage allows us at restricting the interval to MIS 11. Moreover, applying a recently validated conceptual model accounting for an aggradational mechanism linked with sea-level rise during glacial termination for the sedimentary successions of the Tiber River and its tributaries in a relatively wider area around Rome, we further constrain the age to 430–405 ka. Following this approach, we present a review of the archaeological sites of Latium yielding bone instruments, remarking that only other four sites have been recently provided with geochronological constraints, through the application of the multidisciplinary methodology applied here.